Cuban health care : the ongoing revolution - Fitz, Don E., 1948- (Monthly Review Press, 2020)
"Cuba has transformed its health care to the extent that this "third-world" country has been able to maintain a first-world medical system, whose health indicators surpass those of the United States at a fraction of the cost. Don Fitz combines his knowledge of Cuban history with decades of on-the-ground experience in Cuba to tell the story of how Cuba's health care system evolved and how Cuba is tackling the daunting challenges to its revolution in this century"--